Revisiting Classical Criminology: A Moral Perspective on Juvenile Delinquency - Chitov, Alexandre Nikolaevich; Jenroumjit, Wannaphat (CMU Journal of Law and Social Sciences, 2024)
Many scholar works critically examine classical criminology from a mainstream criminological perspective. This paper reverses this approach, offering a critical evaluation of mainstream criminology’s methods in studying juvenile delinquency, viewed through the lens of classical criminology. Unlike the common association with Beccaria or Bentham, classical criminology represents an ethical approach to understanding crime, emphasizing moral realism in the juvenile justice system. It posits that certain fundamental moral principles are essential for any juvenile system. Despite its marginalisation in contemporary discourse, with only a few advocates for its revival, classical criminology challenges mainstream criminologists to consider juvenile criminal justice from a moral standpoint, assessing both the whole and its part in terms of ethical values. This paper explores the fundamental differences between classical and mainstream criminology, despite their use of similar methods. The distinction lies in their philosophical foundations. Classical criminology perceives youth crime as a moral deficiency and views criminal law as a means to promote virtue. This perspective significantly contrasts with the common belief that criminal law is solely a tool for social control. The paper argues that while criminology can be employed as an instrument of harsh control and oppression, it also has the potential to liberate young individuals from criminal behaviors, showcasing its multifaceted nature.